Congestive ischemic colitis occurring after resection of left colon cancer: 4 case series - Takatsugu Fujii; Shigeo Toda; Yuki Nishihara; Yusuke Maeda; Kosuke Hiramatsu; Yutaka Hanaoka; Rikiya Sato; Shuichiro Matoba; Masashi Ueno; Hiroya Kuroyanagi (Surgical Case Reports, 2020)
Abstract Background Ischemic colitis can occur after colectomy and is sometimes difficult to treat. We report 4 cases of refractory, delayed onset, regional congestive colitis occurring on the anal side of the anastomosis after laparoscopic left hemicolectomy. Case presentation A total of 191 patients underwent surgery for left colon cancer (transverse, descending, and sigmoid colon cancer) at our hospital from January 2012 to December 2017. During the procedures, the left colic artery (LCA) or sigmoid colic artery (SA) was dissected, the superior rectal artery (SRA) was preserved, and the inferior mesenteric vein (IMV) was dissected at the inferior margin of the pancreas. Congestive ischemic colitis due to venous return dysfunction occurred in 4 cases (2.1%), 5 to 34 months postoperatively. The patients had diarrhea and blood in the stool. On computed tomography (CT), the patients exhibited continuous intestinal edema and high-density adipose tissue from the anastomosis site to the rectum. Contrast enhancement showed dilation of the vasa recti and arteries from the inferior mesenteric artery (IMA) to the SRA. Three patients improved with long-term intestinal rest; in 1 case, the stenosis did not improve and required colorectal resection. Conclusion Diagnoses were easy in these cases, but treatment was prolonged and surgery was necessary in 1 case. While this condition is rare, caution is warranted as it is difficult to treat.